The Evaluation of Effective Risk Factors in Infant Developmental Disorder - Farin Soleimani; Hossein Karimi (University of Social Welfare and Rehabilitation Sciences, 2005)
Objective: Growth and development are considered as complex and special issues. Growth is increase in body size or segments but development is changing in function that can be affected by environmental factors.Developmental evaluation is very important at infancy because of high growth and developmental rate in this period. It is well known that incidence of developmental disorder in high risk infants are higher than low risk ones and special follow up to be needed for such early detections and furtherly a proper intervention. The purpose of this study was to determine, risk factors influency such developmental delay during an infancy period. Materials & Methods: In this descriptive- analytical study, we screened 6150 in consecutive 4-18 months infants during 12 months period that referred from Karaj health centers for vaccination or monthly follow up by perinatal evaluating questionnaire and examining by Infant Neurological International Battery Test by occupational therapists on two groups: Control (Normal Scoring) and Case (Abnormal Scoring). Results: The results showed that CNS problems after 2 months of age such as siezure disorder, meningitis with (odds ratio=5.54),neonatal convulsion with (odds ratio=4.37), Prematurity with (odds ratio=2.52) and neonatal sepsis with 2.39 are the most important risk factors for developmental disorder. Conclusion: In aspect of results of this study and increasing survival of high risk neonates with biological and environmental risk factors and effectiveness of early intervention(rehabilitation & treatment) if there are any economic problems on Neuro-developmental Screening and Follow-up in our country, we propose such intervention only for High Risk infants.